2015
DOI: 10.1080/17461391.2014.992478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender on trunk and pelvis control during lateral movements with perturbed landing

Abstract: In lateral reactive movements, core stability may influence knee and hip joint kinematics and kinetics. Insufficient core stabilisation is discussed as a major risk factor for anterior cruciate ligament (ACL) injuries. Due to the higher probability of ACL injuries in women, this study concentrates on how gender influences trunk, pelvis and leg kinematics during lateral reactive jumps (LRJs). Perturbations were investigated in 12 men and 12 women performing LRJs under three different landing conditions: a movab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…However, we failed to nd gender-based differences in knee kinetic or kinematics. Instead, female subjects showed larger hip external rotation angle at IC than male subjects as similar to previous studies [26,27]. Since hip internal rotation is a part of dynamic knee valgus motion and associated with larger knee abduction moment [4,28], increased hip external rotation would diminish dynamic knee valgus motion and knee abduction moment.…”
Section: Discussionsupporting
confidence: 88%
“…However, we failed to nd gender-based differences in knee kinetic or kinematics. Instead, female subjects showed larger hip external rotation angle at IC than male subjects as similar to previous studies [26,27]. Since hip internal rotation is a part of dynamic knee valgus motion and associated with larger knee abduction moment [4,28], increased hip external rotation would diminish dynamic knee valgus motion and knee abduction moment.…”
Section: Discussionsupporting
confidence: 88%
“…Perturbed lateral reactive jumps yielded significantly different segment and joint configurations. This influence of LRJ modality has already been described in the literature (24,34). Moreover, during perturbed lateral reactive jumps, the trunk and pelvis positioning Although significant, these changes in trunk lateral flexion and pelvis lateral tilt were rather small given the standard error of the measurements (0.7° and 1.3°, respectively).…”
Section: Discussionsupporting
confidence: 62%
“…The markers (∅14 mm) were placed on the suprasternal notch, the transition between the body of the sternum and the xiphoid process, the T6 vertebra, the anterior and posterior superior iliac spines, the great trochanter, medial and lateral epicondyles of the knee, the tibia (two markers), the medial and lateral malleoli, the first and fifth metatarsal head, the second proximal phalange, and the posterior, medial, and lateral aspects of the heel cup, respectively. This marker placement was used in previously published articles for the lower limb (Gehring et al., ) and the trunk (Mornieux et al., ; Weltin et al., , ). A 12‐camera motion analysis system (Vicon V‐MX, VICON Motion System Ltd., Oxford, UK) was used to record marker trajectories at a sampling frequency of 200 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Training programs addressing the development of motor programs specific to lateral movements should enable athletes to control trunk and pelvic motion together with lower limb alignment during athletic maneuvers (Weltin et al., ). It has been shown that a warm‐up program targeting, for instance, core stability would reduce the rate of ACL injury in adolescent female football players (Walden et al., ).…”
mentioning
confidence: 99%